Caracterização do padrão de mutações dos genes LEPRE1, CRTAP, PPIB, FKBP10, WNT1, SP7, SERPINF1 em osteogênese imperfeita - Trancozo, Maíra (2016)
The Osteogenesis Imperfecta (OI) or brittle bone disease is a hereditary disorder of connective tissue that contains collagen in your training. More than 15 distinct genes causing recessive forms have been reported in recent. Mainly related to genes encoding proteins responsible for post-translational modification of collagen I. In order to characterize the pattern of mutations in genes related to recessive pattern of osteogenesis imperfecta we analyzed the genes LEPRE1, CRTAP, PPIB, SP7, SERPINF1, FKBP10 and Wnt1 which exhibit higher mutation frequency of 22 patients presently described non-consanguineous through Next Generation Sequencing and Sequencing Sanger of patients with clinical diagnosis of osteogenesis imperfect from Espírito Santo assisted at Hospital Infantil Nossa Senhora da Glória de Vitória/ES. Potentially pathogenic changes were found in LEPRE1 e FKBP10 genes in five patients. Two patients carries missense mutations in heterozygous states on LEPRE1 gene (c.1087 A>G e c.2024 G>T changes). The other three patients carry mutations on FKBP10 gene. Two of them have frameshift changes in homozygozity (c.825dupC e c.15dupC) and the last one carries two mutations in compound heterozygozity (c.A179C e c.1063+2T>C). The clinical aspects of the disease in these patients change the moderated to grave. The results suggest that the majority of mutations that causing OI with autosomal recessive inheritance in patients from ES are localized on LEPRE1 e FKBP10 genes. Moreover, according to the results, mutations on CRTAP, PPIB, SP7, SERPINF1 and WNT1 genes are rare on studied population. The characterization of mutation on genes that causing OI on different populations can help to improve our knowledge about the pattern of genetic changes in OI. Furthermore these kinds of studies can help in the design of strategies more efficient that be able the molecular diagnosis of the disease and genetic counseling with families.